Light quality in micropropagation of Eucalyptus grandis × Eucalyptus urophylla - Costa Souza, Denys Matheus Santana; Fernandes, Sérgio Bruno; Avelar, Maria Lopes Martins; do Prado Frade, Samira Rangel [UNESP]; Molinari, Letícia Vaz; Gonçalves, Douglas Santos; Pereira Pinto, José Eduardo Brasil; Brondani, Gilvano Ebling (Instituto de Pesquisa e Estudos Florestais (IPEF), 2020)
The importance of eucalypts species and their interspecific hybrids has been evidenced in forestry programmes due to their wood quality and adaptation to diverse environmental conditions. To solve the limiting factors in the in vitro cultivation of the A211 clone of Eucalyptus grandis Hill ex Maiden × Eucalyptus urophylla S. T. Blake, the aim of the study was to evaluate the light quality on in vitro establishment, multiplication, elongation and rooting stages. The tissues used to obtain explants were nodal segments derived from ministumps of the A211 clone. The effects of light quality on in vitro establishment, multiplication, elongation and rooting were evaluated using five sources (fluorescent lamp, white LEDs, red LEDs, blue LEDs and red/blue LEDs). At 30 days, the percentage of contamination and non-responsive explants, length and number of shoots per explant, oxidation, shoot vigor, pigment content, leaf anatomy, root length and number of roots per explant were evaluated. Fluorescent lamps and red/blue LEDs are more suitable for use in the in vitro establishment, multiplication, elongation and rooting of the A211 clone, without hindering the development of shoots for the production of micropropagated clonal plants.
Qualidade de luz na micropropagação de Eucalytpus grandis × Eucalyptus urophylla
Keywords: In vitro propagation; LEDs, Cloning; Wave-length